2014
DOI: 10.1093/nar/gku821
|View full text |Cite
|
Sign up to set email alerts
|

Structural and energetic characterization of the major DNA adduct formed from the food mutagen ochratoxin A in the NarI hotspot sequence: influence of adduct ionization on the conformational preferences and implications for the NER propensity

Abstract: The nephrotoxic food mutagen ochratoxin A (OTA) produces DNA adducts in rat kidneys, the major lesion being the C8-linked-2′-deoxyguanosine adduct (OTB-dG). Although research on other adducts stresses the importance of understanding the structure of the associated adducted DNA, site-specific incorporation of OTB-dG into DNA has yet to be attempted. The present work uses a robust computational approach to determine the conformational preferences of OTB-dG in three ionization states at three guanine positions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(81 citation statements)
references
References 81 publications
4
77
0
Order By: Relevance
“…Most importantly, our work points toward the effects of the intrinsic adduct conformation on GGR recognition and repair propensity. If verified by future experimental studies, our results will likely expand the list of previously identified factors that affect the structure and repair propensity of adducted DNA, such as substitution at the carcinogen–base linkage ( 47 ), stereochemistry ( 29 , 48 49 ), adduct ionization state ( 50 ), sequence context ( 35 , 47 ) and the identity of the partner base ( 51 ).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Most importantly, our work points toward the effects of the intrinsic adduct conformation on GGR recognition and repair propensity. If verified by future experimental studies, our results will likely expand the list of previously identified factors that affect the structure and repair propensity of adducted DNA, such as substitution at the carcinogen–base linkage ( 47 ), stereochemistry ( 29 , 48 49 ), adduct ionization state ( 50 ), sequence context ( 35 , 47 ) and the identity of the partner base ( 51 ).…”
Section: Introductionsupporting
confidence: 58%
“…To the best of our knowledge, no example exists in the literature of N2-dG adducted DNA in such a conformation. Nevertheless, this structure is analogous to the syn base−displaced intercalated conformation observed for damaged DNA corresponding to several C8-dG adducts ( 47 , 50 , 71 72 ) in terms of the (major groove) extrahelical opposing cytosine. However, damaged guanine is displaced towards the major groove in C8-dG adducted DNA versus the minor groove in ALII-N 2 -dG adducted DNA.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The resulting N-linked C8-dG adducts contain a flexible amine tether separating the dG component from the aryl ring and there is a strong established relationship between the resulting conformational heterogeneity and biological effects ( 5 , 6 ). The structurally related aromatic organic carcinogens, such as polycyclic aromatic hydrocarbons (PAHs) ( 7 9 ), arylhydrazines ( 10 – 12 ) and phenols ( 13 16 ), may also undergo bioactivation, producing aryl radical species that covalently attach to the C8-site of dG to produce carbon-linked C8-aryl-dG adducts. In these cases, the adducts are similar in structure to their N-linked counterparts in terms of aryl ring size and shape, but do not have an amine linkage, thereby altering the orientation of the modification in the DNA duplex as well as reducing conformational flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…25 In contrast to N-linked C8-dG adducts, C-linked lesions tend to induce B-type conformation, although conformational heterogeneity is observed depending on the size of the C8-aryl ring, 26 the nature and placement of substituents on the C8-aryl ring, 27 and the adduct ionization state. 28 Thus, C-and Nlinked adducts have different mutagenic outcomes. For example, in contrast to the nonmutagenic N-linked C8-aniline-dG adduct, 25 the single-ringed C8-phenyl-dG ([Ph]G) adduct induces transversion and frameshift mutations 26,29 and strongly blocks the progress of DNA replication by high-fidelity DNA polymerases: Klenow fragment exo − (Kf − ) 26,29 and DNA pol α.…”
Section: ■ Introductionmentioning
confidence: 99%